A study on factors that would affect employee’s motivation to stay within Naza / Nur Fadilah Ahmad Saifudin - Ahmad Saifudin, Nur Fadilah (2010)
Employee motivation is a complex and sophisticated subject. Organizations around the world are facing similar business challenges which are the difficulty of attracting talent and retaining quality employees. In a human resources context, turnover or labour turnover is the rate at which an employer gains and losses employees. When looking at this problem area we found that there may be actions that companies can use to face this problem as to motivate their employees. The past researcher shows that there are many factors that affect the employee’s motivation. Present research study on three factors that could be the tools that can motivate employees to stay which is compensation and benefits, recognition and work environment. This study has been conducted within Naza and it involved 50 respondents in different department. Results of the present study showed that the most influential factors that affects employee’s motivation to stay within Naza is work environment. Its also shows that work environment has a positive correlation relationship with employee’s motivation in Naza. Recommendations for future research are also have been discussed.